2023
DOI: 10.1186/s13054-022-04253-0
|View full text |Cite
|
Sign up to set email alerts
|

The rate and assessment of muscle wasting during critical illness: a systematic review and meta-analysis

Abstract: Background Patients with critical illness can lose more than 15% of muscle mass in one week, and this can have long-term detrimental effects. However, there is currently no synthesis of the data of intensive care unit (ICU) muscle wasting studies, so the true mean rate of muscle loss across all studies is unknown. The aim of this project was therefore to systematically synthetise data on the rate of muscle loss and to identify the methods used to measure muscle size and to synthetise data on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 74 publications
(133 reference statements)
2
45
0
2
Order By: Relevance
“…We defined muscle wasting as a loss of muscle mass due to aging or any underlying illness with or without decreases in muscle function or fat tissue wasting. [2][3][4] Based on previous studies, [22][23][24] we included studies that reported muscle mass loss of any severity under any definition criteria. The detailed information on cut-off points of muscle wasting for all included studies was presented in Table S2.…”
Section: Definition Of Muscle Wastingmentioning
confidence: 99%
“…We defined muscle wasting as a loss of muscle mass due to aging or any underlying illness with or without decreases in muscle function or fat tissue wasting. [2][3][4] Based on previous studies, [22][23][24] we included studies that reported muscle mass loss of any severity under any definition criteria. The detailed information on cut-off points of muscle wasting for all included studies was presented in Table S2.…”
Section: Definition Of Muscle Wastingmentioning
confidence: 99%
“…The underlying causes of sarcopenia include malnutrition, inactivity, and disease, as well as drugs and hospital admission 2 . Skeletal muscle quality is thus not only lost with old age (primary sarcopenia) but also in association with diseases such as cancer, 5 type 2 diabetes, 6 cardiovascular disease, 7 chronic obstructive pulmonary disease, 8 chronic kidney disease, 9 advanced liver disease, 10 as well as with acute and chronic critical illness 11 . Obesity is an important risk factor for these chronic disorders, and disease‐related secondary sarcopenia also occurs in individuals with excess body fat 12 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] These patients often experience muscle weakness contributing to ICU-acquired weakness (ICU-AW), which is associated with functional limitations, decreased independence and reduced quality of life. 4 Although there is no consensus on how to quantify muscle changes in critically ill patients, 5 ICU-AW is present in up to 75% of mechanically ventilated and critically ill patients, [6][7][8][9][10][11][12] and is more pronounced in older adults, owing to baseline weaker muscle including sarcopenia, 8,11,[13][14][15] frailty 16 and age-associated risk of adverse health outcomes. 17 Sepsis, COVID-19, systemic inflammation, sedation, mechanical ventilation, muscle paralysis and immobilization all contribute to the development of ICU-AW.…”
Section: Introductionmentioning
confidence: 99%